2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696654
|View full text |Cite
|
Sign up to set email alerts
|

Sling bag and backpack detection for human appearance semantic in vision system

Abstract: In many intelligent surveillance systems there is a requirement to search for people of interest through archived semantic labels. Other than searching through typical appearance attributes such as clothing color and body height, information such as whether a person carries a bag or not is valuable to provide more relevant targeted search. We propose two novel and fast algorithms for sling bag and backpack detection based on the geometrical properties of bags. The advantage of the proposed algorithms is that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The body-part method spatially localizes the CO area at a specific location based on body proportions and camera position [6]. Various kinds of CO can be detected by utilizing the general position of the CO carried based on the bend line.…”
Section: G Body-partmentioning
confidence: 99%
See 1 more Smart Citation
“…The body-part method spatially localizes the CO area at a specific location based on body proportions and camera position [6]. Various kinds of CO can be detected by utilizing the general position of the CO carried based on the bend line.…”
Section: G Body-partmentioning
confidence: 99%
“…In addition, backpacks are often confused for one another because many look similar. Research that developed a backpack detection model in video surveillance was reported in [6]- [9]. However, the performance of these methods still needs to be improved so that they can be widely used [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Branca et al [1] work, two classifiers are trained to detect two types of tools that are often used by intruders on archaeological sites. They use the wavelet transform coefficients of a binary foreground blob as features to feed the classifier and search around a person body to detect COs. Chua et al [13] detected sling bag and backpack using their geometrical shape cues (e.g., sling bag straps can be described as two near-parallel lines). Yue et al [14] modeled the spatial relation of points on the person contour to the person main axis using Support Vector Machine (SVM) to classify backpacks and luggage.…”
Section: Related Workmentioning
confidence: 99%
“…Until now different methods of carrying object detection have been proposed. One of them (1) defines geometrical properties of backpack and sling bag strap with Hough transform and edge detection method. In this method, geometrical properties are separately calculated.…”
Section: Related Workmentioning
confidence: 99%